2022
DOI: 10.3390/cancers14174285
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Acetylsalicylic Acid Treatment in Non-Skull-Base Meningiomas: Impact on Tumor Proliferation and Seizure Burden

Abstract: MIB-1 index is an important predictor of meningioma progression and was found to be correlated with COX-2 expression. However, the impact of low-dose acetylsalicylic acid (ASA) on MIB-1 index and clinical symptoms is unclear. Between 2009 and 2022, 710 patients with clinical data, tumor-imaging data, inflammatory laboratory (plasma fibrinogen, serum C-reactive protein) data, and neuropathological reports underwent surgery for primary cranial WHO grade 1 and 2 meningioma. ASA intake was found to be significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…The present literature review confirmed that our findings are consistent with other studies showing a correlation between irregular shape and the MIB-1 labeling index, indicating that shape may serve as a potential quantitative imaging-derived feature to estimate the MIB-1 labeling index. In addition, anti-inflammatory drugs that selectively or non-selectively inhibit COX-2 have been demonstrated to reduce tumor growth and the MIB-1 labeling index [ 55 , 56 ]. However, the molecular classification of meningiomas according to their shape remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The present literature review confirmed that our findings are consistent with other studies showing a correlation between irregular shape and the MIB-1 labeling index, indicating that shape may serve as a potential quantitative imaging-derived feature to estimate the MIB-1 labeling index. In addition, anti-inflammatory drugs that selectively or non-selectively inhibit COX-2 have been demonstrated to reduce tumor growth and the MIB-1 labeling index [ 55 , 56 ]. However, the molecular classification of meningiomas according to their shape remains unknown.…”
Section: Discussionmentioning
confidence: 99%